2010
DOI: 10.1159/000320999
|View full text |Cite
|
Sign up to set email alerts
|

A Special Terpene Combination (Rowatinex®) Improves Stone Clearance after Extracorporeal Shockwave Lithotripsy in Urolithiasis Patients: Results of a Placebo-Controlled Randomised Controlled Trial

Abstract: Objective: To investigate the safety and efficacy of a special terpene combination in the treatment of patients with urolithiasis after extracorporeal shockwave lithotripsy (ESWL). Patients and Methods: 222 patients with clinically stable kidney or ureter stones of 0.3–2.0 cm undergoing complication-free ESWL were randomised to receive a special terpene combination (Rowatinex®; 3 × 2 capsules/day) or placebo. The study consisted of a 12-week active treatment phase and a 2-week follow-up phase. All patients had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Previous studies have reported that Rowatinex can help with the removal of remnant stone after SWL [10]. Rowatinex is an essential oil of terpenic type that consists of pinene (3%), camphene (15%), borneol (10%), anethol (4%), and cineol (3%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported that Rowatinex can help with the removal of remnant stone after SWL [10]. Rowatinex is an essential oil of terpenic type that consists of pinene (3%), camphene (15%), borneol (10%), anethol (4%), and cineol (3%).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of remnant stone formation originating after SWL might increase the long-term success rate of SWL [16]. In addition, Rowatinex has shown antibacterial effects against a variety of pathogens [10]. Rowatinex has anti-inflammatory and analgesic properties derived from cineole and anethole, which are important to patients who have urolithiasis with spasm, inflammation, pain, and infection [17,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When surgery or pharmacologic therapies fail, appropriate chemical treatments may provide a useful adjunct for improving the efficacy of stone comminution during therapy [9] and are typically delivered via a nephrostomy tube. Currently, hemiacidrin and tromethamine have been shown to be efficacious agents both in vitro and in clinical trials [10,11], and the terpene combination facilitated the elimination of stone fragments [12]; however, the dissolution of calcium oxalate stones is complicated by the fact that most of them are hard and large and with non-uniform formations.…”
Section: Discussionmentioning
confidence: 99%
“…[7] Another study designed to investigate the safety and efficacy of a special terpene combination in the treatment of patients with urolithiasis after extracorporeal SWL (ESWL) revealed that it was a well-tolerated, safe, and efficacious therapy for eliminating calculi fragments generated by ESWL when compared to a placebo treatment. [8] Undoubtedly, it is crucial to optimize health care for nephrolithiasis by choosing an ideal treatment that is economical for patients, but still safe and effective. Therefore, the objective of this study was to compare the treatment costs and treatment durations between Rowatinex ® and DSE in patients suffering from nephrolithiasis in Vietnam.…”
mentioning
confidence: 99%